Media Digital Unity 2D: A Study of Teachers' Perspectives on Its Impact on the Learning Motivation of Students with Hearing Impairments - Suarti, Siti; Sujarwanto, Sujarwanto; Watini, Watini (GRAB KIDS: Journal of Special Education Need, 2025)
This research discusses the exploration of perspectives on the impact of using Unity 2D digital media in increasing the motivation of deaf learners. Starting with the communication and accessibility challenges of learners, the use of Unity 2D digital media is believed to be an effective tool to increase learners' participation and enthusiasm. With interactive features and eye-catching visualizations, Unity 2D can create a learning atmosphere that is fun, immersive, and beneficial to learners' understanding. This research applies a qualitative approach using a case study method. Data were collected through in-depth interviews to explore teachers' views on the use of Unity 2D digital media in an effort to increase students' learning motivation. The research report illustrates that teachers' perspectives on the use of Unity 2D digital media have a positive impact towards empowering the learning motivation of students with hearing disabilities. The learning process is delivered in a visualized manner with an interactive and educational display that has an impact on increasing students' learning motivation. As an evaluation material for learning improvement, teachers are encouraged to participate in various online or offline activities related to strengthening digital literacy competencies.